2016
DOI: 10.1038/srep30226
|View full text |Cite
|
Sign up to set email alerts
|

Lutein acts via multiple antioxidant pathways in the photo-stressed retina

Abstract: Lutein slows the progression of age-related macular degeneration (AMD), a leading cause of blindness in ageing societies. However, the underlying mechanisms remain elusive. Here, we evaluated lutein’s effects on light-induced AMD-related pathological events. Balb/c mice exposed to light (2000 lux, 3 h) showed tight junction disruption in the retinal pigment epithelium (RPE) at 12 h, as detected by zona occludens-1 immunostaining. Substantial disruption remained 48 h after light exposure in the vehicle-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 42 publications
1
64
0
1
Order By: Relevance
“…1 Previous studies have shown that b-alanine treatment administered in the drinking water at a concentration of 3% causes a decline in taurine plasma levels [34][35][36] and in tissues such as the hippocampus, posterior cortex, and retina, as well as in cellular taurine content 13,14,[37][38][39][40] and also that taurine depletion causes loss of retinal neurons 6,41-43 (see below). [50][51][52] Light is a risk factor for some retinal degenerations, [53][54][55][56] and it accelerates photoreceptor degeneration in some inherited retinal degenerations. 54,[57][58][59] In previous work, [18][19][20]50 we documented that light exposure causes rapid photoreceptor degeneration and, longterm, alterations in all the retinal layers and RGC loss.…”
Section: Discussionmentioning
confidence: 99%
“…1 Previous studies have shown that b-alanine treatment administered in the drinking water at a concentration of 3% causes a decline in taurine plasma levels [34][35][36] and in tissues such as the hippocampus, posterior cortex, and retina, as well as in cellular taurine content 13,14,[37][38][39][40] and also that taurine depletion causes loss of retinal neurons 6,41-43 (see below). [50][51][52] Light is a risk factor for some retinal degenerations, [53][54][55][56] and it accelerates photoreceptor degeneration in some inherited retinal degenerations. 54,[57][58][59] In previous work, [18][19][20]50 we documented that light exposure causes rapid photoreceptor degeneration and, longterm, alterations in all the retinal layers and RGC loss.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence is characterized as an inability to proliferate despite the presence of sufficient nutrients but where cell viability and metabolic activity are still maintained (8). It is also a process through which cells undergo phenotypic changes, including chromatin alterations, tumor suppression, and interruption of cell division (9). Senescence is triggered by extreme cellular stress and may act as a protective mechanism against malignant cell degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Senescence is triggered by extreme cellular stress and may act as a protective mechanism against malignant cell degeneration. Common triggers for the onset of senescence are telomere shortening and dysfunction, DNA damage, oxidative stress, chromatin perturbations, oncogene activity, and strong mitogenic signals (7,9). Thus, common traits of senescent cells are altered cell morphology, cell cycle arrest, DNA damage, tolerance to apoptosis, inflammatory protein secretion, activation of tumor-suppressing mechanisms, and changes in gene expression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human RPE (hRPE) cells are frequently used in in vitro studies to investigate RPE-related disesases, as well as specific clinical treatments for these diseases. Thus, the hRPE cell line ARPE-19 was used in our study [2, 5, 6]. …”
Section: Introductionmentioning
confidence: 99%